Keadilan dan Niat Keberlangsungan Nasabah Pasca Serangan Siber: Peran Kepuasan Pemulihan Layanan - Susanti Sinta Rini; Farid Hidayat; Akhmad Yusuf Khoiruddin; Mahfud Asyari (Universitas Islam Raden Rahmat, 2025)
The development of digitalisation is increasing, especially in the banking sector. This is an opportunity for hackers to hack into the system and steal data to demand ransom. This study aims to analyse the effect of Distributive Justice, Procedural Justice, and Interactional Justice on customers' sustainable intention to use BSI after cyber-attacks with service recovery satisfaction as an intervening variable. The object of this research is customers domiciled in the Special Region of Yogyakarta. This research is primary data with data collection techniques using questionnaires and 168 respondents were obtained. This research method uses SEM-SmartPLS version 3.0. The results found from this study indicate that only Procedural Justice, and Interactional Justice have a significant effect on the sustainability intention of BSI customers after cyber-attacks with service recovery satisfaction as an intervening variable.